Design and evaluation of novel tetracyclic benzofurans as palm site allosteric inhibitors of HCV NS5B polymerase. Issue 24 (15th December 2019) - Liu, Hong; Dai, Xing; He, Shuwen; Brockunier, Linda; Marcantonio, Karen; Ludmerer, Steven W.; Li, Fangbiao; Feng, Kung-I; Nargund, Ravi P.; Palani, Anandan
Graphical abstract: Highlights: N-linked and C-linked tetracyclic benzofuran-based compounds were made and evaluated as HCV 5B non-nucleoside inhibitors. Tetracyclic benzofuran-based structures maintained broad spectrum anti-replicon potency profiles. Compounds demonstrated moderate to excellent oral bioavailability and pharmacokinetic parameters. C-linked tetracycle with 6-number ring displayed improved solubility and permeability compared to a clinical compound. Abstract: Hepatitis C virus (HCV) NS5B polymerase is a prime target for the development of direct-acting antiviral drugs for the treatment of chronic HCV infection. Several novel and potent HCV NS5B non-nucleoside inhibitors with unique tetracyclic bezonfuran-based structures were prepared and evaluated. Similar to clinical developmental compound MK-8876, N-linked (compounds 1 and 2 ) and C-linked (compounds 3 and 4 ) tetracyclic structures maintained broad spectrum anti-replicon potency profiles and demonstrated moderate to excellent oral bioavailability and pharmacokinetic parameters across the three preclinical animal species. To better understand the importance of tetracyclic structures related to pan genotypic potency profiles especially against clinically relevant GT1a variants, the teracycles with different ring size were prepared and in vitro evaluations suggested compounds with six number ring have better overall potency profiles.